Undergraduate Students’ Mathematical Problem-Solving Ability in Solving PISA-like Problems - Yuni Apriani; Dede Suratman; Nurfadilah Siregar; Bistari; Edy Yusmin (Universitas Ahmad Dahlan, 2025)
Mathematical problem-solving ability was an essential competence, yet many undergraduate students still faced difficulties when confronted with non-routine problems in PISA. This study aimed to describe the mathematical problem-solving abilities of 5th-semester Mathematics Education undergraduates in solving a PISA-like problem with shape content at level 6, which represented the highest level of mathematical proficiency in PISA. Using a qualitative approach, data were collected through a PISA-like problem and interviews, then analysed through data reduction, data display, and conclusion drawing. The results showed that 20% of students had high problem-solving ability, 53.33% medium, and 26.67% low. High-category students met all problem-solving indicators. Medium-category students reached the carrying out the plan indicator but skipped looking back. Low-category students only met the understanding the problem indicator and struggled to identify appropriate strategies and formulas. The study concluded that most students were in the medium category, with limited mastery of higher indicators.